Varying ethnicity of students potentially improve the ability of the group in completing bacteriology practice projects - Didimus Tanah Boleng; Elsje Theodora Maasawet; Hariska Swandana (University of Muhammadiyah Malang, 2023)
Student ethnicity is one of the internal factors that influence student learning. Bacteriology is a course that examines prokaryotic unicellular living things and is practiced in laboratories that need to implement projects. The aim of this research is to know the distribution of students based on their ethnicity. The research sample was students who programmed the bacteriology course in the Biology Education Study Program at Mulawarman University, in the even semester of the 2022/2023 academic year. The sampling technique is purposive sampling. The research instrument is a questionnaire. The data analysis technique is percentage. The results of the data analysis show that there are various student ethnicities. There are four ethnic groups that dominate other ethnic groups, namely: Javanese (25.5%), Bugis (18.8%), Kutai (16.4%), and Banjar (14.9%). Completion of projects in groups whose members are heterogeneous based on ethnicity allows the participation of every member of the group. The conclusion is that there are various student ethnicities who program bacteriology courses, namely those consisting of ethnic Javanese, Bugis, Kutai, Banjar, Berau, Toraja, Paser, Mandar, Batak, Palembang, and Dayak. It is necessary to add a larger sample size for similar research in order to obtain more information.